First Major Abdominal Surgical Case of Full-blown AIDS in Thailand - Tanchanpong, Chana; Jivapaisarnpong, Paiboon (Journal of Health Science of Thailand, 1992)
Abdominal pain in AIDS patients was not common, but some of these cases might be surgically correctable, as shown by the case in this report. A thin, Thai man, 49 years old, was infected with blood transmitted HIV in his second operation for bleeding duodenal ulcer. Two years later he developed full-blown AIDS, with chronic muco-cutaneous Herpes simplex virus infection of buccal mucosa and larynx. He was admitted for several times within 2 subsequent years because of opportunistic infection and abdominal pain. In the last admission, he had abdominal pain, nausea and fatique. Hepatomegaly as well as epigastric tenderness was detected on examination. Ultrasonographic examination revealed multiple gall stones; and large antral and stomal ulcers were also found on gastroscopic examination. His clinical status was deteriorated, the abdominal pain had increased in intensity. Therefore, an operation was considered. Operative findings wereempyema gall bladder, antral and stomal ulcers. Cholecystectomy and subtotal gas-trectomy were done. His post operative days were uneventful and he was discharged on the 9th operative day.